Shenkang injection in the treatment of diabetic nephropathy at stage Ⅲ: A systematic review and meta-analysis - WANG Jing-wen; ZOU Xin-rong; DING Xiu; YUAN Hua-ping; YUAN Meiling; WANG Xiao-qin (Linchuang shenzangbing zazhi)
Objective To systematically evaluate the clinical effectiveness and safety of Shenkang injection(SKI) in the treatment of diabetic nephropathy(DN) at stage Ⅲ. Methods Seven English and Chinese databases(up to Mar. 25,2018),were searched to collect the clinical researches on SKI for DN stage III. Two researchers independently screened the literatures and evaluated the quality of the literatures according to the Cochrane Reviewer’s Handbook 5. 1. Stata 14. 0 was used for the meta-analysis. Results In terms of effectiveness,a total of 10 studies involving686 patients were included. The meta-analysis results showed that compared with the control group,the experimental group with SKI performed better in reducing the urinary albumin excretion rate[SMD =-1. 29,95% CI(-1. 77,-0. 80),P < 0. 05 ],serum creatinine [SMD =-0. 86,95 % CI(-1. 54,-0. 18),P < 0. 05 ],cystatin c [SMD =-1. 87,95 % CI(-2. 40,-1. 34),P < 0. 05 ],with no statistically significant difference in the quantitative test of 2 4-h urinary protein [SM D =-4. 7 5,9 5 % C I(-1 0. 5 0,1. 0 0),P > 0. 0 5] and blood urea nitrogen[SMD =-0. 01,95 % CI(-0. 39,0. 38),P > 0. 05] between two groups. In terms of safety,7 studies w ere included,and no serious adverse events/adverse events(ADR/AE)w ere found. Conclusions The m eta-analysis results show ed that SKI for DN stage Ⅲ treatm ent could reduce the urinary album in excretion rate and im prove renal function. H ow ever,due to the lim ited num ber and quality of studies included in this m eta-analysis,the above conclusions still need to be confirm ed by m ore high-quality,large-sam ple,m ulti-center clinical studies. Although the system atic evaluation has not yet found the severe ADR/AE in the treatm ent of DN stage Ⅲ by SKI,the safety assessm ent of SKI for clinical use still needs to be em phasized and carried out.